Juridical Overview on the Inconsistency of Prohibition to be the Member of Political Parties for the Members of Public Institutions - Fajar Prima Julian; Ratna Herawati (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2021)
The creation of a justice in the life of the nation and state must be supported by regulations that do not conflict with other regulations. The prohibition to join a political party for administrators of public institutions is in conflict with higher regulations. The article is considered contrary to the principle of